The Effect Of Sports On The Attention Levels Of Primary School Students - Osman İmamoğlu; Yener Aksoy; Hüseyin Aslan (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the effect of sports on the attention levels of primary school students. Participants were 150 female and 170 male Primary education students aged 12-14 years. Student's t-test was used for paired categorical comparisons between the groups. While there was a statistically significant difference between girls and boys in terms of psychomotor speed, selective attention level and special learning difficulty values (p lt;0,05), no statistically significant difference was found for concentration performance and total item error percentages (p gt; 0, 05). While there was no statistically significant difference between the psychomotor speed scores of both boys and girls in the comparison between sport group and non-sport group (p gt; 0.05), there was a statistically significant difference in the level of selective attention, learning disability, concentration performance and total item error percentage (p lt;0.05 and p lt;0.001). Conclusion: It was determined that the attention levels of primary school students doing sports were better than those who were not doing sports. In the study, girls’ psycho-motor speed scores and selective attention level scores were higher than boys’ scores. Special learning disability scores were higher in boys than girls. It is recommended that all students in primary schools be involved in sporting activities to raise their attention levels.